Hydrogen evolution by a low cost photocatalyst: bauxite residue - Mangrulkar, Priti A.; Joshi, Meenal V.; Kamble, Sanjay P.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
Bauxite residue or red mud which is an aluminium industry waste has been used as a novel low cost photocatalyst active in visible light for the generation of hydrogen from water. The driving force behind the use of bauxite residue as a photocatalyst is not only the fact that it is widely available but also bauxite residue is a fine grained mixture of oxides and hydroxides (Fe(2)O(3), TiO(2), SiO(2), and Al(2)O(3), Al(OH)3). The photocatalyst was characterized with respect to BET-SA, UV-DRS, XRD, SEM and EDX. Hydrogen yield of 4600 mu mol/h/g of TiO(2) was achieved as compared to hydrogen evolution rate of 164 mu mol/h/g of TiO(2) for commercially available titania Degussa P-25. However, the hydrogen evolution was 20.85 mu mol/h/g of photocatalyst. The results suggest that bauxite residue appears to be a novel low cost photocatalyst. The various operating conditions of photocatalytic hydrogen generation were studied which include amount of catalyst, illumination intensity, illumination time, effect of various sacrificial donors etc. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Aluminium industry waste; Bauxite residue; Hydrogen generation; Red mud; Sacrificial donors